Intraoperative Assessment of the Relationship Between Nipple Circulation and Incision Site in Nipple-Sparing Mastectomy With Implant Breast Reconstruction Using the SPY Imaging System. (February 2018) - Wang, Chi-Yu; Wang, Chin-Hsin; Tzeng, Yuan-Sheng; Lin, Chin-Ta; Chou, Chang-Yi; Chiang, I-Han; Wu, Chien-Ju; Chen, Shyi-Gen
Abstract : Introduction: Nipple-sparing mastectomy (NSM) and immediate breast reconstruction with gel implants have grown in popularity because of superior aesthetic outcomes. One risk of this procedure is overexcision of the flap leading to inadequate circulation in the breast envelope. Methods: We investigated 17 cases of NSM and gel implant breast reconstruction. Patients were divided into an infra-areolar incision group and a supra-areolar incision group. Nipple-areolar complex perfusion was evaluated using the SPY imaging system after NSM and gel implant breast reconstruction. We aimed to discover any relationships between the incision method and nipple-areolar complex (NAC) circulation in NSM and gel implant breast reconstruction. Results: For successful breast surgery, awareness of the blood supply to the breast, especially the NAC, is very important. In our study, with the indocyanine green SPY imaging system, most ingress (arterial inflow) and egress (venous outflow) rates in the infra-areolar incision group were better than those in the supra-areolar incision group ( P < 0.005). Conclusions: We have shown that an infra-areolar incision provides better blood flow following NSM and gel implant breast reconstruction. In our experience, in order to prevent the possible ischemia of NAC, we used the smaller gel implants, which is approximately 10 to 20 mL smaller than the original implant size measured by the sizer, if the egress rate of NAC is lower than 0.2. These findings have implications in the clinical setting as surgeons have a choice to provide a better outcome for patients.